Dexmedetomidine regulates the anti-oxidation and autophagy of adipose-derived stromal cells under H2O2-induced oxidative stress through Nrf2/p62 pathway and improves the retention rate of autologous fat transplantation - Li, Zihao; Wei, Qing; Li, Yijun; Yang, Fangfang; Ke, Chen; Li, Tian; Li, Liqun; Cai, Zhongming (Frontiers in Pharmacology, 2024)
To investigate the protective mechanism of dexmedetomidine (DEX) on adipose-derived stromal cells (ADSCs) under oxidative stress model and its promotion effect on the retention rate of adipose granule transplantation by in vitro and in vivo experiments. The experiment was divided into control group, model group (ADSCs+H2O2+normal serum), DEX group (ADSCs+H202+DEX drug-containing serum), autophagy agonist group (ADSCs+H2O2+rapamycin (RAP)+normal serum), RAP+DEX group (ADSCs+H2O2+normal serum) ， RAP+DEX drug-containing serum), autophagy inhibitor group (ADSCs+H2O2+chloroquine (CQ)+normal serum), CQ+DEX group (ADSCs+H2O2+CQ+DEX drug-containing serum). HO-1, GSH-PX, SOD and CAT in ADSCs under oxidative stress model were measured. ROS fluorescence intensity and apoptosis ratio were detected. Expression of Nrf2, LC3-II/LC3-I and p62 were detected. In vivo, fat mixed with ADSCs or DEX -pretreated ADSCs was implanted subcutaneously in the lower back region of nude mice. Fat grafts were collected and analyzed at 2-, 4-, 6-, and 8-weeks post-transplantation. DEX pretreatment could reduce the expression of p62 to enhance the autophagy level of ADSCs under oxidative stress model. Additionally, cotransplantation of DEX-pretreated ADSCs with fat improved the long-term texture of fat grafts. DEX increased the fat graft survival and angiogenesis.